1986
DOI: 10.1143/ptps.87.102
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Antiferromagnetic Potts Models

Abstract: Phase transitions of antiferromagnetic Potts models are investigated by cactus approximations and Monte Carlo simulations. These models show phase transitions associated with highly degenerate ground states. By the simulations for systems on a simple cubic lattice, a Kosterlitz-Thouless phase has been found below kT/ IJI::::e 1.25 for the three-state Potts model, while a longrange ordering consisting of two sublattices has appeared below k T/ If I : : : : e 0. 7 for the four-state Potts model. by guest on Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…1a around the y axis) with a radius increasing with decreasing temperature. Apparently, the relevant order parameter in the critical region close to T c would be z r , which actually was used for the susceptibility calculations in previous MC calculations [4,5,11]. This result is consistent with the reported XY universality class: The free energy of the XY model is rotationally symmetric in ͗s x ͘, ͗s y ͘ space at any temperature.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…1a around the y axis) with a radius increasing with decreasing temperature. Apparently, the relevant order parameter in the critical region close to T c would be z r , which actually was used for the susceptibility calculations in previous MC calculations [4,5,11]. This result is consistent with the reported XY universality class: The free energy of the XY model is rotationally symmetric in ͗s x ͘, ͗s y ͘ space at any temperature.…”
supporting
confidence: 84%
“…Because of incomplete ordering [2] at T 0 these points never actually reach the edges. What Ono [5] found during a relatively short MC run was a very broad distribution of the instantaneous order parameter on this phase space instead of gathering around a single point, which indicates wide (or shallow) free-energy minima even well below T c . More accurate Monte Carlo simulations by Wang et al [4] based on a cluster-flip algorithm have shown that while at low temperature there clearly exist six freeenergy minima, where the order parameter points gather, corresponding to the BSS phase, at higher temperatures the distribution is more rotationally symmetric with some sixfold anisotropy, and very close to T c the distribution is almost circular (see Fig.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, according to numerical calculations, there appears to be an intermediate phase below T c and above the low-temperature phase. While there have been various proposals [5][6][7] for the intermediate region, most reliable numerical results at present indicates that the intermediate region appears to be rotationally symmetric phase which is similar to the ordered phase of the 3D XY model [10][11][12] . However, the "transition" between the intermediate region and the low-temperature phase is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Since the numerical method (20) becomes less precise near the critical line, we expand the mean-field free energy F 0 in powers of the order-parameter to investigate the critical behavior.…”
Section: Effective Free Energy Formmentioning
confidence: 99%